Significance of Plant Growth Promoting Rhizobacteria in Grain Legumes: Growth Promotion and Crop Production - Karivaradharajan Swarnalakshmi; Vandana Yadav; Deepti Tyagi; Dolly Wattal Dhar; Annapurna Kannepalli; Shiv Kumar (Plants, 2020)
Grain legumes are an important component of sustainable agri-food systems. They establish symbiotic association with rhizobia and arbuscular mycorrhizal fungi, thus reducing the use of chemical fertilizers. Several other free-living microbial communities (PGPR—plant growth promoting rhizobacteria) residing in the soil-root interface are also known to influence biogeochemical cycles and improve legume productivity. The growth and function of these microorganisms are affected by root exudate molecules secreted in the rhizosphere region. PGPRs produce the chemicals which stimulate growth and functions of leguminous crops at different growth stages. They promote plant growth by nitrogen fixation, solubilization as well as mineralization of phosphorus, and production of phytohormone(s). The co-inoculation of PGPRs along with rhizobia has shown to enhance nodulation and symbiotic interaction. The recent molecular tools are helpful to understand and predict the establishment and function of PGPRs and plant response. In this review, we provide an overview of various growth promoting mechanisms of PGPR inoculations in the production of leguminous crops.